The Comparison of Functional Capacity Improvement after Pulmonary Rehabilitation between COPD Groups with Different Exacerbation History - Budiati Laksmitasari; Siti Chandra Widjanantie; Nury Nusdwinuringtyas (Indonesian Journal of Physical Medicine & Rehabilitation, 2019)
Backgrounds: Pulmonary rehabilitation may improve functional capacity in chronic obstructive pulmonary disease (COPD). This study aimed to know the effect of 2-month pulmonary rehabilitation in the functional capacity of the patient with stable COPD and compare the functional capacity change based on exacerbation history. Methods: This was retrospective cohort study. The subjects were patients with stable COPD who underwent pulmonary rehabilitation in Persahabatan National Respiratory Hospital, between February 2018 and January 2019. Functional capacity was evaluated by 6-minute walking distance (6MWD) before and after 2-month pulmonary rehabilitation. The 6MWD change was compared between COPD group A-B and group C-D. Results: Of the 14 subjects, the 6MWD was significantly improved in all subjects (p=0.001). The median of 6MWD change was 32 (6-235) m. The 6MWD improvement was 35 (7-84) m in COPD group A-B and29 (6-235) m in COPD group C-D. There was no significant difference in 6MWD improvement between both groups (p=1.000). Conclusion: Two-month pulmonary rehabilitation may improve functional capacity in the patient with stable COPD regardless of the exacerbation history.